2014
DOI: 10.1007/s40596-014-0256-y
|View full text |Cite
|
Sign up to set email alerts
|

A Process-Oriented Approach to Teaching Religion and Spirituality in Psychiatry Residency Training

Abstract: The findings suggest improvement in competency and professional practice scores in residents who participated in this course. This points toward the overall usefulness of the course and suggests that a process-oriented approach may be effective for discussing religion and spirituality in psychiatric training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 13 publications
0
44
0
Order By: Relevance
“…However, caution is recommended when using these treatments, as this is a private and personal matter that should be considered but not used as a prescription [ 68 ]. In addition, some doctors do not feel prepared to integrate R/S in clinical practice [ 69 71 ]. These observations endorse the necessity of introducing the R/S topic into medical schools to clarify the clinical implications and professional conduct in the field [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, caution is recommended when using these treatments, as this is a private and personal matter that should be considered but not used as a prescription [ 68 ]. In addition, some doctors do not feel prepared to integrate R/S in clinical practice [ 69 71 ]. These observations endorse the necessity of introducing the R/S topic into medical schools to clarify the clinical implications and professional conduct in the field [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Except for three of the included studies, the residents were in the third year, 15,18,20 and at least one psychiatrist mentioned the profile of the coordinators. [13][14][15]18,22 A total of 31 methods and 23 different topics were found in the categorized results. 10 The residents' assessment was summative and formative, quantitative and qualitative.…”
Section: Resultsmentioning
confidence: 99%
“…Further details of this systematic review can be found elsewhere. 10 The eleven selected studies [13][14][15][16][17][18][19][20][21][22][23] were evaluated according to the following seven categories: residency year in which the intervention was implemented, course coordinator/faculty teaching methods, topics covered, evaluation tools and results (for the curriculum, residents, and patients), R/S competencies addressed, and recommended bibliography.…”
Section: Methodsmentioning
confidence: 99%
“…Suggestions for improvement included more skills training and more teaching about different religions. Some were aware that an evening elective existed for this purpose, 21 but most could not attend.…”
Section: Physicians' Reflections Regarding the Curriculum (Theme 4)mentioning
confidence: 99%